Genetic Assessment of a Black Rockfish, Sebastes schlegelii, Stock Enhancement Program in Lidao Bay, China Based on Mitochondrial and Nuclear DNA Analysis - Wang, Lijuan; Wu, Zhihao; Wang, Yingjun; Liu, Mengxia; Song, Aihuan; Liu, Hongjun; You, Feng (Frontiers in Marine Science, 2020)
The black rockfish Sebastes schlegelii is a commercially important fish species for marine fishery stock enhancement in Asia. This work aimed to evaluate the potential genetic impacts of releasing hatchery-reared juvenile black rockfish on wild stock in Lidao Bay, China. A partial sequence of the mitochondrial DNA (mtDNA) control region and 38 microsatellite DNA loci were used to assess the genetic impact. The haplotype diversity parameter (h) and nucleotide diversity parameter (π) in hatchery-released stock were 0.902 and 0.00483, respectively. The h values in wild stock before stock enhancement and the mixed stock after enhancement were 0.970 and 0.939 (p = 0.025), respectively, and the π values were 0.00581 and 0.00526 (p = 0.150), respectively. The mean effective number of alleles (Ae) in hatchery-released stock was 4.76, the mean polymorphism information content (PIC) was 0.674, the observed heterozygosity (Ho) was 0.668, and the expected heterozygosity (He) was 0.697. In wild stock before stock enhancement and the mixed stock after enhancement, the Ae, PIC, Ho, and He values were 6.01 and 5.82, 0.698 and 0.716, 0.709 and 0.741, and 0.735 and 0.754, respectively. These results indicated no marked decrease in the hatchery-released stock, although it displayed slightly lower levels of genetic diversity and heterozygosity than the wild stock. And the mixed stock after release exhibited similar genetic diversity to that of the wild stock before release. Accordingly, we propose that stock enhancement may not cause genetic diversity reduction on wild S. schlegelii stock in Lidao Bay over the short term. Whereas, discriminant analysis of principal components (DAPC) analysis identified three major clusters. The fixation index (FST) and analysis of molecular variance (AMOVA) also clearly showed low level but significant differentiations between the hatchery-released and wild stocks, and the wild stock before enhancement and the mixed stock after enhancement. Consequently, long-term genetic evaluation might be required.